2021
DOI: 10.3389/ffutr.2021.722812
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emerging ICT in the Ports: Increasing Utilities According to Shared Decisions

Abstract: Geographical location, infrastructures, and services are the main consolidated pillars of a port in terms of its capacity to compete and cooperate with other ports. In the last years, a new pillar was identified: emerging technologies. Ports’ issues were initially solved with individual ICT solutions adopted by each decision-maker, which generated efficiencies in the three main port flows: cargo, information, and financial. However, new benefits and challenges are connected with the introduction of shared emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In city logistics, this is not an exception, and the tendency to use electronic collaboration is increasing day by day. Therefore, the future research directions should be devoted toward the development of an integrated platform for innovative city logistics, creating unified space for all the stakeholders with the emerging technologies like the ones built in the port communities with the Port Community System (PCS; Moros-Daza et al, 2020;Russo and Musolino, 2021). The city logistics community system could be defined as an interorganizational system used for enabling commercial services and providing information exchange between the freight receivers (e.g., end consumers and retailers) and a variety of actors, such as transport and logistics operators (e.g., carriers and couriers), among others, under the rules defined by public administrations.…”
Section: City Logistics Actorsmentioning
confidence: 99%
“…In city logistics, this is not an exception, and the tendency to use electronic collaboration is increasing day by day. Therefore, the future research directions should be devoted toward the development of an integrated platform for innovative city logistics, creating unified space for all the stakeholders with the emerging technologies like the ones built in the port communities with the Port Community System (PCS; Moros-Daza et al, 2020;Russo and Musolino, 2021). The city logistics community system could be defined as an interorganizational system used for enabling commercial services and providing information exchange between the freight receivers (e.g., end consumers and retailers) and a variety of actors, such as transport and logistics operators (e.g., carriers and couriers), among others, under the rules defined by public administrations.…”
Section: City Logistics Actorsmentioning
confidence: 99%
“…However, it was not possible to associate the PCS described to any specific wave. [21], [25]  Logistics and transport (L&T): logistics and transport of goods from land to sea (and vice versa) by road and rail transport (short and long distances);  Customs (CU): import and export, administrative and custom control processes;  Navigation (NA), management and planning of ship arrivals and departures;  Dangerous goods (DG), traffic of dangerous goods, and related procedures.…”
Section: B Pcs Wave (Emerging Ict)mentioning
confidence: 99%
“…Today fifth generation of ports is characterized by the use of emerging information and communication technologies (ICT) in the interaction between port stakeholders. The introduction of emerging ICT inside ports has shown that ICT is a further pillar of port competitiveness alongside the traditional ones as the port closeness to the cities or to the industrial plants, and the capacity to generate added value, the dotation of infrastructures and shared services (see Russo and Musolino [21], [22] and references included).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), influencing the behaviour of people at individual and collective way. Some applications are proposed in the field of city logistics [25] and of ports and maritime transport [26], [27].…”
Section: Learning Process In Presence Of Emerging Ictmentioning
confidence: 99%